Development of a shape‐controlled H2S delivery system using epoxide‐functional nanoparticles. Issue 18 (23rd April 2019) - Yu, Sul Hwa; Esser, Lars; Khor, Song Yang; Senyschyn, Danielle; Veldhuis, Nicholas A.; Whittaker, Michael R.; Ercole, Francesca; Davis, Thomas P.; Quinn, John F.
ABSTRACT: Hydrogen sulfide (H2 S), an endogenous modulator of signaling processes, has potential as a therapeutic drug or in combination drug therapies. Due to its broad biological impacts and malodorous nature, there is considerable interest in vehicles capable of delivering H2 S in a controlled manner. Herein, we report postpolymerization modification of polymers incorporating glycidyl methacrylate (GMA) units to form thiol‐triggered macromolecular H2 S donors. By combining this approach with polymerization‐induced self‐assembly, this methodology allows the facile preparation of polymeric nanoparticulate donors with either spherical or worm‐like morphology. The thiol‐reactive epoxide functional groups in poly(GMA) were chemically transformed into acyl‐protected perthiol groups using a three‐step procedure throughout which both morphologies remained intact. The H2 S releasing properties were subsequently studied, with both spherical and worm‐like nanoparticulate donors shown to successfully release H2 S in the presence of the model thiol, l ‐cysteine. In addition, the donor polymers were shown to effectively increase H2 S inside cells, upon exposure to biologically relevant endogenous thiol levels. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1982–1993 Abstract : The authors present the facile preparation of hydrogen sulfide (H2 S) releasing worm‐like and spherical micelles using a postassembly modification approach. The methodology combines polymerization‐induced self‐assembly (PISA) with ring opening of incorporated epoxide rings. The materials prepared are shown to release H2 S upon exposure to a suitable trigger (l ‐cysteine) or when introduced to the cellular milieu. The results demonstrate the utility of PISA for preparing gasotransmitter‐emitting nanoparticles of variable morphology.